Eksistensi Media Lokal di Kota Medan Dalam Persaingan Ekosistem Informasi Digital - Topan Bilardo (Journal of Social Media and Message, 2026)
Digital transformation has significantly changed the media industry landscape, including for local media in Medan. This study aims to analyze the existence of local media in the face of competition in a digital information ecosystem dominated by global platforms and national online media. The method used was a systematic literature review, examining various scientific journals, industry reports, and publications related to digital media. The results of the study indicate that local media in Medan face challenges such as technological disruption, changes in audience behavior, and the dominance of digital platform algorithms. However, local media still have opportunities through a hyperlocal journalism approach, multi-platform adaptation, and strengthening information credibility. This study confirms that the sustainability of local media is highly dependent on innovative digital strategies and the relevance of locally based content.